2021
DOI: 10.1155/2021/6651020
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antibacterial Characterization of Endophytic Fungi from Artemisia sieberi

Abstract: Endophytic fungi serve as a reservoir for important secondary metabolites. The current study focused on the antibacterial properties of endophytic fungi isolated from Artemisia sieberi. Initially, six endophytic fungi were isolated and purified from the stem of A. sieberi. Endophytic fungi were identified by morphological characteristics, as well as by molecular identification using 18S rRNA gene sequencing method. All the six isolates were subjected to the preliminary screening for their antibacterial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Medicinal plants i.e., Artemisia are potential hosts to surplus advantageous endophytes. Artemisia is a genus of plants highly valued as a source of metabolites useful in, for example, medicine and biopesticides 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants i.e., Artemisia are potential hosts to surplus advantageous endophytes. Artemisia is a genus of plants highly valued as a source of metabolites useful in, for example, medicine and biopesticides 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…32 A recent study examined the antimicrobial activity of six fungal isolates against 9 bacterial pathogens and the results concluded that more susceptibility to the active compounds was observed for Gram-positive bacteria. 33 Identification of the potent fungal isolate (F3) F 3 w a s e x p o s e d t o m o l e c u l a r characterization and had a multiple alignment with the highest homology using blast search computer based program on NCBI platform. The identified sequence was deposited in NCBI as Aspergillus terreus SHE05 with accession no.…”
Section: Results and Discussion Isolation Of Marine Fungi And Screening For Antibacterial Potentialitymentioning
confidence: 99%
“…Proteus mirabilis is considered a human pathogen which infects the urinary tract, especially in people who have long-term hospitalization [ 34 , 35 ]. Previous research [ 36 ] found that P. chrysogenum has the superior antibacterial activity against nine bacterial species, including Escherichia coli , Acinetobacter baumannii , and Staphylococcus aureus , when compared to Aspergillus oryzae and Aspergillus niger . Furthermore, the fungus inhibited Pseudomonas aeruginosa growth significantly [ 37 ].…”
Section: Discussionmentioning
confidence: 99%